Habenaria agasthyamalaiana (Orchidaceae), a new terrestrial orchid from the Southern Western Ghats, India - Jalal, Jeewan Singh (Universidad de Costa Rica, 2019)
Habenaria agasthyamalaiana, a new species of terrestrial orchid is described from Shendurney Wildlife Sanctuary of Agasthyamalai biosphere reserve, a part of the South-western Ghats. This species is morphologically similar to Habenaria crinifera Lindl. Detailed description and photographs are provided for identification of this new taxon.